Development of skinless beef longanisa using optimum levels of binders - Chua, Mary Junel P.
The study was conducted to develop an acceptable skinless beef longanisa formulation using different binders. It was divided into two phases. Phase I which dealt with the development of an acceptable skinless beef longanisa formulation was divided into three subphases. In Phase IA, sensory evaluation and percent cooking loss determination was conducted on a control and three experimental skinless beef longanisa containing different kinds of binders namely: Isolated soy protein (ISP), Carrageenan and Sodium caseinate. This was done to evaluate the effectivity of the addition of binders and at the same time to determine the best suitable binder/s. In Phase IB, eight laboratory-scale skinless beef longanisa formulations using the combination of three different binders were developed by the Plackett and Burman experimental design. In Phase IC, two Mixture Design experiments were used to obtain an optimum level of the combination of different binders. From the series of formulation experiments in Phase I, the final formula with the optimum level of binder was developed. This formula called for 1.0% ISP, 0.5% carrageenan and 2.0% sodium casienate. Phase II was divided into two subphases. In Phase IIA, the best laboratory-scale production formulation from Phase IC was translated to the pilot scale. The final skinless beef longanisa was found to have the following attributes: reddish brown color, very tender, very juicy and slightly to distinct beef flavor. The panelists ranked the final product as "liked very much." After two weeks of storage, the final product was found to be positive for Coliforms and Salmonellae. This was not so alarming since the product is categorized under fresh, frozen meat products. The total Plate Count was2.5 x 10^5 cfu/gm below the maximum allowable limit for frozen meat products. The cost analysis resulted to a recommended selling price of P2.52 for each skinless beef longanisa weighing about 30 grams. Phase IIB standardized the formula and process by establishing the important quality control points, product specifications and control procedures.